Role of innate immune responses in the effectiveness of oncolytic adenovirus as an anticancer agent. (23rd February 2017) - Leung, Elaine Y; Weigert, Melanie; Walton, Josephine B; Ennis, Darren P; Athineos, Dimitris; Dowson, Suzanne; Hansell, Chris; Blyth, Karen; Graham, Gerard; McNeish, Iain A
Abstract: Background: Ovarian cancer is the deadliest gynaecological cancer, with fewer than half of patients surviving for more than 5 years. Oncolytic viruses have been investigated as a new class of anticancer agent for this and other cancers. Oncolytic viruses infect and replicate selectively within malignant cells, while sparing normal cells. These viruses also induce profound immune responses, which might influence clinical efficacy. In this study we investigated the role of innate immune responses, in particular interleukin (IL) 17F, on the effectiveness of oncolytic adenovirus. Methods: Changes in key human chemokines and cytokines in ovarian cancer lines (TOV21G, OVCAR4) after infection by the E1A CR2-deleted oncolytic adenovirus dl 922-947 were identified by PCR array (RT 2 Profiler, Qiagen, Hilden, Germany), a transcriptional screen. The observed changes were confirmed by real-time PCR and ELISA in six primary lines derived from malignant ovarian ascites ex vivo (primary lines) and by real-time PCR in human cancer xenografts in CD1 nu/nu mice (n=12). TOV21G IL17F −/– cells were generated with CRISPR–Cas9 technology (ThermoFisher, Waltham, MA, USA). Findings: dl 922-947 infection led to consistent changes of chemokines and cytokines transcription ( r =0·56, p<0·0001). The most highly upregulated cytokine was IL17F (167-fold change in TOV21G [p<0·0001] and 98 in OVCAR4 [p=0·02]). IL17F, but not IL17A, was also increased in primary lines (92-fold change, p=0·03) and TOV21G xenografts infected with dl 922-947 in vivo (23, p=0·02). Moreover, upregulation of IL17F was confirmed by ELISA in TOV21G (n=2 in triplicates, p<0·05) and in primary lines (2086 pg/10 6 vs 1381, p=0·03). IL17F has previously been implicated in neutrophil recruitment. Significant neutrophil infiltration was observed after dl 922-947 infection in HeLa subcutaneous xenografts by immunohistochemistry (median histoscores 2 for mock and 16·5 for tumours infected with dl 922-947, p=0·01). Interpretation: Oncolytic adenovirus infection led to distinctive changes in chemokines and cytokines. In particular, IL17F, but not IL17A, was upregulated after adenovirus infection in vitro and in vivo. Moreover, dl 922-947 infection was associated with neutrophil infiltration in vivo. Ongoing experiments with TOV21G IL17F −/– cells generated using CRISPR–Cas9 technology will elucidate the influence of IL17F upregulation on tumour immune microenvironment and the effectiveness of dl 922-947. Funding: Wellcome Trust.